Microplastic ingestion by fish with different feeding habits in the Ob and Yenisei Rivers - Vorobiev, Danil S.; Frank, Yuliya A.; Rakhmatullina, Svetlana N.; Vorobiev, Egor D.; Poskrebysheva, Yulia R.; Oladele, Oyeleye; Trifonov, Andrey A. (Вестник Томского государственного университета. Биология)
Microplastic particles in the size range 0.15 to 5.00 mm were quantified and characterised in the gastrointestinal tracts of three wild freshwater fish (n = 141) from the Ob and Yenisei rivers, including common ruffe (Gymnocephalus cernua L.), Siberian dace (Leuciscus baicalensis Dybowski) and European perch (Perca fluviatilis L.). Microplastics were found in the gastrointestinal tract of 62% of the fish examined, ranging from 18.5% in the Yenisei perch sample to 92.6% in the Ob ruffe sample. The vast majority of microplastics in all fish species were fibres (up to 99.7% of all particles detected in perch), followed by irregularly shaped fragments (up to 22.7% in ruffe), with no preference between the three species. Spheres and films were found exclusively in dace and ruffe, with proportions of 3.7% and 1.2% respectively. Particles consisted of polyethylene terephthalate, polypropylene, polyamide and other synthetic polymers with a significant proportion of highly degraded polymers. The mean MP content in fish GITs ranged from 0.44 ± 0.25 items per individual in Yenisei perch to 3.81 ± 0.55 items per individual in Ob ruffe. Particle burdens in fish were significantly higher in the Ob than in the Yenisei (p < 0.05), which may reflect the common level of plastic contamination in these two rivers. MP ingestion varied in species with different feeding habits as ruffe (benthivorous) > dace (omnivorous) > perch (hunter) in both rivers (p < 0.01). This study was the first to quantify MP consumption by freshwater fish of different species in the Ob and Yenisei rivers and to identify patterns associated with different feeding habits.